Ureteroscopic lithotripsy in the Trendelenburg position for extracting obstructive upper ureteral obstruction stones: a prospective, randomized, comparative trial. (4th July 2018) - Zhou, Rongsheng; Han, Conghui; Hao, Lin; Chen, Bo; Zang, Guanghui; Fan, Tao; Zhou, Jiahe; Dong, Yang; Ma, Weiming; Pang, Kun
Abstract: Objective: To introduce a new position for ureteroscopic holmium laser lithotripsy for patients with upper ureteral calculi. Materials and methods: Between June 2014 and May 2017, 192 patients were enrolled in this study. Patients were randomly assigned to one of two groups: group A, ureteroscopic lithotripsy (URSL) in the Trendelenburg position; or group B, URSL in the standard position. Baseline information, including gender, age, body mass index (BMI), stone side, stone size and hydronephrosis grade, was collected and determined preoperatively. Stone-free rate (SFR) was evaluated 3 weeks after surgery and was defined by the absence of residual stones or the presence of residual stones <2 mm in diameter. Operation time, hospital stay, stone migration, operative complications and SFR were assessed and compared between the two groups. Results: There were no statistically significant differences in gender, age, BMI, stone side, stone size, serum creatinine or hydronephrosis grade between the two groups (all p  > 0.05). There were no significant differences in the postoperative hospital stay or postoperative complications between the two groups (all p  > 0.05), but the differences in operative time, stone migration and SFR between the two groups were statistically significant ( p  < 0.05). Conclusion: This study introduced a new position for ureteroscopic holmium laser lithotripsy for patients with upper ureteral calculi. The Trendelenburg position can improve the SFR and may provide an optional surgical method for treating upper ureteral calculi.